Enhancement of resistance to bacterial wilt in tomato by endophytic microbial communities - Deepa James (Department of plant pathology, College of horticulture, 2015)
The study on “Enhancement of resistance to bacterial wilt in tomato by endophytic microbial communities” was conducted in the Department of Plant Pathology, Department of Agricultural Microbiology, and Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, Vellanikkara during the period 2011-2014. The endophytes were isolated from root and stem of healthy tomato plants from 16 locations of north, central and south Kerala. Endophytic microbial population varied with the plant samples and the population was more in root than stem. Bacterial population was higher than fungi and actinomycetes in root and stem. Among 154 endophytes isolated, 12 out of 79 bacteria, 16 out of 68 fungi, and four out of seven actinomycetes were antagonistic to R. solanacearum in in vitro. Among them, five bacteria, eight fungi, and two actinomycetes were promising in planta. Mutually compatible endophytic isolates were selected for the development of consortia and these were identified based on cultural, morphological and molecular characters. Of the five consortia tested, the one consisted of Trichoderma viride-1, T. viride-2, T. harzianum-1, Bacillus subtilis, and Streptomyces thermodiastaticus showed effect in reducing wilt incidence. Comparative study of the microbial consortium with individual endophytes showed the higher efficacy of consortium in reducing the wilt incidence. The endophytes were reisolated from soil, root, and stem of tomato plants. In pot culture experiment, the consortium applied as seed treatment + seedling dip + soil application at 45 DAP showed the minimum wilt incidence. Studies on the mechanism of antagonism of endophytic isolates showed, positive reaction towards ammonia and negative for HCN and siderophore production. The volatile and nonvolatile metabolites of the endophytes inhibited the pathogen. The endophytes showed varying levels of IAA and salicylic acid production with the maximum in T. harzianum-1 and B. subtilis respectively. Study on the effect of secondary metabolites of endophytes on the disease indicated that, seedlings dipped first in culture filtrate for 2 h and later dipped in bacterial inoculum for 30 min before planting showed the lowest per cent wilt incidence with the minimum for T. viride-2. Induction of systemic resistance was studied by assay of defense related compounds such as phenols, oxidative enzymes and PR proteins. The plants treated with microbial consortium showed higher activity of the defense related compounds with the maximum in plants inoculated with both consortium and pathogen. Field evaluation of endophytic consortium against bacterial wilt showed reduction in wilt incidence of 40.85 per cent in highly susceptible variety, PKM-1, 46.94 per cent in susceptible F1 hybrid, COTH-3, and 52.81 per cent in moderately resistant variety, Mukthi. Thus, the study revealed that, the application of endophytic consortium can enhance the resistance mechanism in tomato against bacterial wilt pathogen, R. solanacearum.